Antibiofilm and antimicrobial activities of papaya (Carica papaya L.) and stevia (Stevia rebaudiana Bertoni) leaf extracts against three biofilm-forming bacteria - Aerma Hastuty (Microbiology Division, Research Center for Biology, Indonesian Institute of Sciences, 2019)
Biofilm is a structural form of a microbial group that is protected by the Extracellular Polymeric Substance (EPS) matrix. The biofilm is considered as the main mediator of infection, and plays a major role in the occurrence of drug resistance. This study was aimed at determining the antimicrobial and antibiofilm activities of papaya (Carica papaya L.) and stevia (Stevia rebaudiana Bertoni) leaf extracts against three biofilm-forming bacteria. The antimicrobial assay showed that papaya leaf extract exhibits higher activity compared to stevia leaf extract in inhibiting the growth of the biofilm-forming bacteria. The optimum condition of papaya leaf extract to inhibit biofilm-forming bacterial growth occurred at 45% and 75% concentrations of the extract (pH 7). A 100% biofilm degradation by papaya leaf extract occurred at pH 6 and pH 9.